Especificação modular de restrições arquiteturais - Sândalo Carleto D'el Rio Euzébio e Bessa (2016)
After years of continuous evolution, it is usual to observe misalignments between code and architecture, leading to a phenomenon known as architectural erosion. DCL (Dependency Constraint Language) is a domain-specific language allowing the specification of architectural rules that must be followed by a system implementation. In this master dissertation, we present an extension of DCL---called DCL 2.0---that provides features supporting the hierarchicaldefinition of modular and reusable architectural rules. We use DCL 2.0 to define architectural rules for a real-world system, maintained by a major public software company from Minas Gerais. We detect 771 architectural violations in this system, which 74% could only be detected due to the new features proposed by DCL 2.0.